Public administration of de-shadowing of the economic system in the conditions of globalization - Nadiia Datsii; George Abuselidze; Olga Zborovska; Roman Zborovskyy; Dmytro Mishchenko; Nadiia Karpeko (E3S Web of Conferences, 2023)
The article proposes to consider a complex process of implementation of the state management measures of de-shadowing of the economic system in the conditions of globalization. The stages of the state policy of de-shadowing of the economic system in the conditions of globalization are substantiated: 1. Construction of the strategy of counteraction to the shadow economy. 2. Organization of legal and legislative bases of the process of counteracting the shadow economy. 3. Implementation of comprehensive measures to reduce the shadow sector. 4. Formation of motives and incentives for work in the legal sector of the economy. 5. Adding the shadow capital to priority sectors of the economy. 6. The growth of the legal sector of the economy. 7. Limiting the scale of the shadow economy. It is noted that the state policy to eliminate the shadowing of the economic system should be based on a systematic approach to the selection of the country's methods of influence on processes, which are implemented in this area, as well as approval and application of the effective instruments to implement the planned measures in practice (direct and indirect). The program of realization of the mechanisms of the state policy of de-shadowing of the economic activity in the conditions of globalization as a dynamic uniform environment is suggested which gives the chance to influence the growth of indicators of the legal sector of economy and unites a complex of operating subsystems.
Keywords: 330; Public policy; Governance; De-shadowing; Economic System; Economic relations; Globalization